USE OF ACTIVATED CARBON FOR WASTEWATER TREATMENT - Kushnazarova Shoxidaxon Kosimovna; Muhammadjonova Naziraxon Ravshanjonovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on wastewater treatment methods